A photo-responsive metallomesogen for an optically and electrically tunable polarized light modulator. Issue 87 (3rd October 2016) - Kim, Dae-Yoon; Kang, Dong-Gue; Lee, Myong-Hoon; Kim, Jin-Soo; Lee, Cheul-Ro; Jeong, Kwang-Un
Abstract : A palladium(ii )-based metallomesogen containing the photo-responsive azobenzene was newly synthesized and was demonstrated to be an optically and electrically tunable polarized light modulator. Abstract : A palladium(ii )-based metallomesogen with azobenzene was synthesized for the fabrication of an optically and electrically tunable polarized light modulator. Owing to the extended molecular geometry constructed by organometallic chemistry, the photo-responsive metallomesogen showed an excellent orientation in liquid crystal media.